The Menyibak Personalisasi "Aku" dalam Bingkai Relasi: Sebuah Refleksi Kritis terhadap Eksistensi Manusia menurut Martin Buber: Konsep 'Aku' dan 'Kau' - Jirin, Marsianus (Hunatech Vol. XXX, No. XXX, 2024)
The focus of this paper is to find the meaning of the relationship between “I” and “Thou” according to Martin Buber's perspective. According to Martin Buber, the I and Thou relationship is a path to self-wholeness through an encounter. The encounter of “I” and “Thou” is based on a dialog to reveal deep meaning towards authentic self-knowledge. Encounter is a daily activity of individual human beings who involve themselves in the shared experience of others, because humans are basically relational beings who are constantly in dialog. Dialogue bridges the interpretation of meaning between “I” and “Thou” based on complete self-disclosure. The presence of “I” and “Thou” is not interpreted as subject-object, but an equal subject in a relational frame. In contrast to I-It, the subject-object relationship, cornering, alienating the other. Here the subject-object relationship is instrumental, thus threatening, intimidating, discriminating the others. The I-It relationship is only objective and separate in a control that gives rise to manipulation. The personalization of the self wants to display the unique sensuality of the I as an equal subject in the presence of other subjects. The encounter between “I” and “Thou” forms a complex experience towards a deep understanding of human existence. The purpose of this paper is to provide a deeper understanding of the meaning of human life in a frame of relationship. The method used is the literature method by collecting A The purpose of this paper is to provide a deeper understanding of the meaning of human life in a frame of relationships. The method used is the literature method by collecting data as a reference to deepen understanding of the themes explored in this article. The findings of this research are that a dialog deepens the relationship between “I” and “Thou” towards a perfect self. Through dialog, “I” can understand others more deeply and comprehensively. Here, the role of “I” as a subject is very decisive as a personalization of self with the others.